EFFECTIVENESS OF E-GOVERNMENT FOR COMMUNITY ADMINISTRATION SERVICE MEDIA - Fithriana, Noora (Universitas Islam Malang, 2025)
Advances in technology and information in the current era are increasingly rapid and affect many aspects of daily life. With various positive impacts, one of which is the use of this technology in terms of administration and public services. Thus, the e-Government program was born, where the community can access independently to take care of all matters relating to population and government administration. One area that uses the convenience of this service is the community of Tunjung Tirto sub-district, Singosari district, Malang district. This study aims to analyze the effectiveness of the implementation of e-Government as a medium for public administration services in Tunjung Tirto village, Singosari district, Malang district. The method used in this study was interviews, with government officials from the sub-district office and the community in Tunjung Tirto sub-district, Singosari district, Malang district as resource persons, as well as literature studies using relevant journals and books. The results of this study indicate that the implementation of the e-Government program in Tunjung Tirto sub-district, Singosari district, Malang district has not been effective. The obstacles that affect are related to internal factors, namely from users and external which are obstacles outside the user. Furthermore, it is expected that e-Government can be used optimally considering the benefits provided will be felt by the government and the community itself, and become the first step and example for other regions to utilize e-Government optimally.